2014
DOI: 10.1371/journal.pone.0107649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oligodendroglial Populations in Mouse Demyelinating Disease Using Flow Cytometry: Clues for MS Pathogenesis

Abstract: Characterizing and enumerating cells of the oligodendrocyte lineage (OLCs) is crucial for understanding demyelination and therapeutic benefit in models of demyelinating disease in the central nervous system. Here we describe a novel method for the rapid, unbiased analysis of mouse OLCs using flow cytometry. The assay was optimized to maximize viable yield of OLCs and maintain OLC antigen integrity. Panels of antibodies were assembled for simultaneous analysis of seven antigens on individual cells allowing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 27 publications
3
44
1
Order By: Relevance
“…2) while maintaining the efficient detection of numerous cell markers (O4,NeuN,CD45,CD11b,CD3,CD4,CD8). Similarly to our results, Robinson et al (2014) obtained the highest cell yield using Accutase, a commercially available mix of proteolytic and collagenolytic enzymes, and other collagenase-based commercial solutions (e.g. Liberase), compared with undigested tissues, or trypsin or papain digested tissues.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…2) while maintaining the efficient detection of numerous cell markers (O4,NeuN,CD45,CD11b,CD3,CD4,CD8). Similarly to our results, Robinson et al (2014) obtained the highest cell yield using Accutase, a commercially available mix of proteolytic and collagenolytic enzymes, and other collagenase-based commercial solutions (e.g. Liberase), compared with undigested tissues, or trypsin or papain digested tissues.…”
Section: Discussionsupporting
confidence: 86%
“…1). One group has also reported that the linear Percoll separation is superior to the Percoll gradient to recover cells of the oligodendrocyte lineage from mouse CNS (Robinson et al, 2014). We found that amongst several digestion conditions (papain + DNase I, trypsin + DNase I, collagenase D + DNase I, and none), the collagenase D + DNase I step allowed the best cell number recovery (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Utilizing analogous antibodies and reporter lines and varied strategies of dissociation, neurons (6)(7)(8)(9)(10), astrocytes (6,7,(10)(11)(12)(13), microglia (6,7,12,(14)(15)(16)(17)(18)(19)(20), endothelia (21,22), and oligodendrocytes (6,7,23,24) have been collected separately. In addition, multiple cell types have been isolated and profiled concurrently by using a combinatorial approach of reporter lines and/or multiple antibodies (1,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]8 Moreover, certain antioxidants such as melatonin, 9 quetiapine, 10 and resveratrol, 11 showed protective effects on the CPZ-induced oligodendrocyte loss and myelin breakdown in recent animal studies. Interestingly, oligodendrocyte loss and myelin breakdown were accompanied by increase in the number of OPCs labeled as NG2 C (chondroitin sulfate proteoglycan) and PDGFRa C (platelet-derived growth factor a) cells in CPZexposed mice, [12][13][14] suggesting the existence of an aberrant cell cycle regulation following CPZ administration.…”
Section: Introductionmentioning
confidence: 99%